Decolonizing ethnography : undocumented immigrants and new directions in social science - Alonso Bejarano, Carolina, 1983-; López Juárez, Lucia; Mijangos García, Mirian A.; Goldstein, Daniel M., 1965- (Duke University Press, 2019)
The coauthors of Decolonizing Ethnography integrate ethnography with activist work in a New Jersey center for undocumented workers, showing how anthropology can function as a vehicle for activism and as a tool for marginalized people to theorize their own experiences.